Effect of pearlite nanoclay reinforcements on the mechanical and tribological behaviour of AA7076 metal nanocomposites (Fracture and Structural Integrity, 2025)
Aluminium alloy composites are extensively utilised in the aerospace, automobile, and marine industries due to their lightweight structure and high strength-to-density ratio. However, there remains significant potential to further improve these composites for advanced applications by enhancing their strength-to-weight ratio, corrosion resistance, wear resistance, and temperature performance. This study investigates the mechanical and tribological properties of AA7076 alloy reinforced with varying concentrations (1.0 and 1.5 wt.%) of perlite nanoclay. These composites were synthesized using a motorised stir casting process and characterised through tensile, wear, and hardness tests. Results showed that 1.5 wt. % perlite nanoclay composite exhibited the most significant improvements, with hardness, tensile strength, and wear resistance increasing by 32%, 38%, and 59%, respectively, compared to the base AA7076 alloy. Finite element simulations in ANSYS Workbench predicted tensile strengths in close agreement (within 5 – 8%) with experimental results, validating the strengthening effects of nanoclay. The enhancements are attributed to the homogeneous dispersion of nanoclay particles, strong interfacial bonding, and their role in restricting dislocation motion. These findings establish perlite nanoclay as a cost-effective and sustainable reinforcement for aluminium alloy, well-suited for demanding applications in automotive, aerospace, and marine industries, offering a promising combination of lightweight design and superior performance.
Keywords: Aluminium matrix composites; pearlite nano clay particle,; stir casting; mechanical and tribological behaviour